Motivasi, Disiplin, dan Beban Kerja terhadap Produktivitas Pegawai Sekretariat DPRD Maluku - Berny Jofranz Metwaan; Hendry Selanno; Josep Antonius Ufi (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This article examines the influence of motivation, work discipline, and workload on employee productivity at the Secretariat of the Regional People's Representative Council (DPRD) of Maluku Province. The study employed a quantitative associative survey design involving 164 employees, with the whole accessible population treated as respondents through a census approach. Data were collected using a Likert-scale questionnaire and analyzed through validity and reliability testing, classical assumption testing, and multiple linear regression. The results show that motivation has a positive but non-significant effect on productivity (B = 0.040; t = 0.518; p = 0.605). In contrast, work discipline has a positive and significant effect (B = 0.293; t = 5.539; p < 0.001), while workload is the most dominant predictor (B = 0.545; t = 6.513; p < 0.001). Simultaneously, the three variables significantly affect productivity (F = 375.829; p < 0.001; Adjusted R2 = 0.873). The findings highlight the need for disciplined work systems, proportional workload management, and output-based productivity monitoring in legislative-support bureaucracy.